The midnight after [videorecording (DVD)] - Chan, Fruit; Wong, You Nam, 1983-; Wen, Yongshan; Yam, Simon (Well Go USA Entertainment, 2016)
Sixteen strangers on a bus, an apocalyptic accident, a downtown full of people: Vanished. The newly-dead: Instantly Decaying. Ominous glimpses of men in gas masks. What's happened to the world, and how far would you go to get your life back?